Determinants of the poor quality of professional life among nurses in six hospitals within the Kongo-Central province of the DRC - NSIMBA , Daniel NZUANDA; Ngoma, Oscar MADEMVO; Koto-Te-Nyiwa Ngbolua, Jean-Paul; Imani, BIN ERADI RAMAZANI; Katuasi, Daniel ISHOSO; Ntela Mabakutuvangila , Simon-Decap; Mukandu, Félicien BASUA (Orapuh Journal, 2025)
Introduction The quality of life at work for nurses, which is essential for their well-being and the provision of quality care, is adversely affected by challenging conditions. These professionals often face difficult working environments and a variety of negative factors. Purpose This study investigates the determinants of the poor quality of professional life among nurses in six hospitals within the Kongo-Central province of the DRC. Methods A cross-sectional, descriptive study of a correlational nature was conducted among 300 nurses across six hospitals in Kongo Central. Data were collected using an electronic questionnaire administered via the Kobocollect platform in the Democratic Republic of the Congo. Results Among the 300 nurses surveyed, 95.7% reported a poor quality of work life. Bivariate analyses revealed that task variety (CI: 1.03–2.11; p = 0.048), workplace accidents (CI: 3.59–219; p < 0.001), mentorship or professional support (CI: 1.09–6.83; p = 0.015), and the absence of parental leave (CI: 1.2–11.35; p = 0.015) were significantly associated with poor quality of work life. Following logistic regression analysis, only institutional mentorship remained strongly associated with poor quality of life at work (adjusted OR: 10.891; CI: 1.181–100.409; p = 0.035). Conclusion The findings of this research underscore the urgent need to improve the professional quality of life for nurses in Kongo Central. Policymakers and hospital administrators must work collaboratively to implement structural and organisational reforms, with particular emphasis on mentorship, prevention of occupational risks, work–life balance, and the recognition of nurses. These measures will positively impact not only the well-being of nurses but also the quality of care and overall performance of hospitals in Kongo Central. Further qualitative studies are recommended to explore these issues in greater depth.